An Alternative Assessment Model to Improve a Translated Text from Indonesian into English - Marwan Tanuwijaya; Aditya Cahyo Nugroho; Pratama Ahdi; Novita Dewi (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2016)
The main aspect of translation is how one’s expression in one language is replaced with an equivalent representation in another language. The representation should be equivalent in terms of its stylistic, referential, and linguistic features. Whether there is a need for a translation text to be classified as